2007
DOI: 10.1111/j.1744-7402.2007.02113.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite–Carbon Nanotube Composites for Biomedical Applications: A Review

Abstract: Hydroxyapatite (HA) has been used in clinical bone graft procedures for more than 25 years. However, its poor tensile strength and fracture toughness compared with bone make it unsuitable for major load‐bearing devices. Carbon nanotubes (CNTs), with their high aspect ratio and excellent mechanical properties, have the potential to strengthen and toughen HA without offsetting its bioactivity, thus opening up a wider range of possible clinical uses for the material. This review discusses techniques for synthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
156
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 374 publications
(159 citation statements)
references
References 83 publications
(105 reference statements)
2
156
0
1
Order By: Relevance
“…Another research group performed compression tests on bulk HA/nanotubes biocomposites and found an increase in strength over single-phase HA [246]. However, the highest compressive strength they achieved for any material was only 102 MPa, which is similar to that of cortical bone but much lower than the typical values for dense HA [874]. More complex formulations, such as poly-L-lysine/HA/carbon nanotube hybrid nanocomposites, have also been developed [884].…”
Section: Biocomposites With Glasses Inorganic Materials and Metalsmentioning
confidence: 99%
See 3 more Smart Citations
“…Another research group performed compression tests on bulk HA/nanotubes biocomposites and found an increase in strength over single-phase HA [246]. However, the highest compressive strength they achieved for any material was only 102 MPa, which is similar to that of cortical bone but much lower than the typical values for dense HA [874]. More complex formulations, such as poly-L-lysine/HA/carbon nanotube hybrid nanocomposites, have also been developed [884].…”
Section: Biocomposites With Glasses Inorganic Materials and Metalsmentioning
confidence: 99%
“…Carbon nanotubes with their small dimensions, a highaspect-ratio (length-to-diameter) as well as the exceptional mechanical properties, including extreme flexibility and strength, significant resistance to bending, high resilience and the ability to reverse any buckling of the tube, have the excellent potential to accomplish necessary mechanical properties [874]. Recent studies have even suggested that they may possess some bioactivity [875][876][877][878].…”
Section: Biocomposites With Glasses Inorganic Materials and Metalsmentioning
confidence: 99%
See 2 more Smart Citations
“…, (White et al, 2007). , 75% , Kim et al, 2003;Trinkunaite-Felsen et al, 2014), (Ma et al, 2003 in vitro in vivo (Parizi et al, 2013;Zhang et al, 2011).…”
Section: 해양무척추동물 유래 의생명공학적 활용 가능 소재mentioning
confidence: 99%